Applying Gamma Ray Radiation on Ciherang Rice Plants (Oryza sativa L.) Growth - Efraim Butar Butar; Siti Hartati Yusida Saragih; Novilda Elizabeth Mustamu; Badrul Ainy Dalimunthe (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
The Ciherang rice variety, favored by farmers for its high productivity and resistance to several diseases, has recently shown a decline in performance due to environmental stress and suboptimal adaptation to climate change. This study aimed to determine the extent to which gamma ray exposure affects the growth of Ciherang rice plants. The research employed an experimental method using a single-factor Completely Randomized Design (CRD) with 10 treatments: 0, 50, 100, 150, 200, 250, 300, 350, 400, and 450 Gy, each repeated three times. Consequently, 30 experimental units were established and analyzed using analysis of variance (ANOVA) with SPSS software, followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results demonstrated that gamma-ray radiation significantly affected plant growth and development, with responses varying according to the administered dose. Notably, the 100 ash treatment consistently outperformed others across the three measured parameters: it exhibited the highest germination rate (71%), the most significant plant height at all observation intervals (21.2 cm at 2 weeks after planting [WAP], 51.33 cm at 4 WAP, and 88.33 cm at 6 WAP), and the highest number of tillers (3.66, 6.66, and 14 tillers at the respective time points).